Exploring eccentric hamstring strength: peak force, torque, and impulse metrics in elite academy soccer players - Tondelli, E.; Tomaghelli, L.; Tedesco, F.; Feroldi, A.; Herbella, J.; Baldjian, A.; Van Dyk, N. (Research Quarterly for Exercise and Sport, 2025)
This study aimed to characterize eccentric strength metrics and the bilateral asymmetry index of the knee flexor muscles across different categories in elite academy soccer players. Also, explore correlations between the metrics with demographic characteristics. With a cross-sectional design, data were collected over two weeks during the mid-year break of the 2023 season. Eccentric muscle strength was assessed with the Nordic Hamstring Exercise (NHE) with the NordBord®. One hundred thirty-two male elite academy soccer players between 13 and 20 years old (16.3 ± 2.2 years; body mass (BM): 68.8 ± 6.5 kg; height: 174 ± 7 cm) competing in the Argentinian Football League participated. Metrics included were relative and absolute peak force (PF), peak torque (PT), and eccentric impulse (EI). Bilateral asymmetry index (BAI) was calculated for each metric. Eccentric PF, PT, and EI significantly increased with age. BAI decreased from the U17 category onward. Moderate correlations were observed between PF and PT with BM (r = 0.45, p < .001, 95% CI: 0.31-0.58; and r = 0.54, p < .001, 95% CI: 0.41-0.65, respectively), and PF with body mass index (BMI) (r = 0.37, p < .001, 95% CI: 0.22-0.51). EI had weaker correlations with BM (r = 0.12, p < .1665, 95% CI: -0.061-0.3). PF and PT peaked at the U17 and declined in older categories. To conclude, this study found higher eccentric hamstring strength values in elite youth soccer players than previously reported. PF showed moderate correlation with BMI, while EI had weak correlations with BM. Significant age-related variations in BAI were observed, particularly in younger players.